Batik Information Based E-Commerce - Dermawan, Abdillah; Siahaan, Yanty Faradillah; Andriana, Septiana Deni (Al'Adzkiya, 2020)
Traditional batik as a cultural heritage contains the value of local wisdom or cultural heritage (heritage) and the art of batik is one of the cultural products known from our ancestors. The sales of batik made by Small and Medium Enterprises (SMEs) in the country are still very potential, and try to expand their sales distribution abroad through export channels. In today's digital era, introducing batik to the world is quite easy. Just post it on social media, people will see it, but that doesn't mean they will understand. Therefore, to help Batik SMEs players in providing an understanding of batik, we need a system in which the system, apart from providing information about batik, can also be used for buying and selling transactions. The development of this system uses the waterfall method and system design uses UML. The result of this research is a website-based application that can be used by batik craftsmen in providing information about batik and also can make buying and selling transactions online.